Exploring the use of the transtheoretical model in psychiatric nursing counseling for women with schizophrenia experiencing intimate partner violence: A clinical case study from Indonesia - Prasetyo Aji Nugroho; Somporn Rungreangkulkij; Muliantika Muliantika (Lentera Perawat, 2026)
Background: Intimate partner violence (IPV) is a major global public health concern associated with severe psychological consequences, particularly among women with pre-existing mental disorders. Survivors with chronic mental illness often experience complex psychological challenges that may hinder recovery and increase vulnerability to repeated abuse. However, structured psychiatric nursing approaches addressing survivors’ readiness for behavioral change remain limited. Objective: This study aimed to explore the application of the Transtheoretical Model of Change within psychiatric nursing counseling for women with schizophrenia experiencing intimate partner violence. Methods: A qualitative clinical case study design was employed involving two female participants with schizophrenia receiving psychiatric nursing care in Indonesia. Data were collected through clinical observation, nursing assessments, therapeutic communication, counseling session documentation, and nursing care records. Counseling interventions were implemented using experiential and behavioral strategies aligned with the stages of change framework. Data were analyzed using thematic content analysis focusing on patterns of psychological responses, coping processes, and behavioral changes observed during counseling.. Results: Clinical observations indicated that experiential strategies, including consciousness raising, self-reevaluation, and dramatic relief, were associated with increased recognition of abusive experiences and reduced self-blaming responses. Behavioral strategies such as self-liberation, reinforcement management, and counterconditioning were observed alongside the development of adaptive coping behaviors, emotional regulation, and greater engagement in daily functioning. Participants demonstrated individual variations in readiness for change throughout the counseling process. Conclusion: Transtheoretical Model may provide a useful framework for tailoring psychiatric nursing counseling according to survivors’ readiness for change and clinical context. However, findings should be interpreted cautiously given the qualitative case study design and small number of participants. Further research involving larger samples and standardized outcome measures is needed to strengthen understanding of stage-based counseling approaches among survivors of intimate partner violence with chronic mental illness.